2016
DOI: 10.1530/rep-15-0561
|View full text |Cite
|
Sign up to set email alerts
|

BCL2-modifying factor promotes germ cell loss during murine oogenesis

Abstract: Apoptosis plays a prominent role during ovarian development by eliminating large numbers of germ cells from the female germ line. However, the precise mechanisms and regulatory proteins involved in germ cell death are yet to be determined. In this study, we characterised the role of the pro-apoptotic BH3-only protein, BCL2-modifying factor (BMF), in germ cell apoptosis in embryonic and neonatal mouse ovaries. BMF protein was immunohistochemically localised to germ cells at embryonic days 15.5 (E15.5) and E17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…BMF is a pro-apoptotic BCL-2 protein family member with documented roles in follicle atresia 5 and in the regulation of germ cell numbers during fetal ovarian development. 32 The current results indicate that apoptosis is central to primordial follicle loss during puberty, and they identify BMF as the key apoptotic trigger. Whether BMF acts directly on primordial follicles or regulates apoptosis in growing follicles (or possibly the ovarian stroma) to indirectly mediate primordial follicle depletion, is not known.…”
Section: Discussionmentioning
confidence: 60%
“…BMF is a pro-apoptotic BCL-2 protein family member with documented roles in follicle atresia 5 and in the regulation of germ cell numbers during fetal ovarian development. 32 The current results indicate that apoptosis is central to primordial follicle loss during puberty, and they identify BMF as the key apoptotic trigger. Whether BMF acts directly on primordial follicles or regulates apoptosis in growing follicles (or possibly the ovarian stroma) to indirectly mediate primordial follicle depletion, is not known.…”
Section: Discussionmentioning
confidence: 60%
“…Deletion of this cluster in germ cells of female mice caused increased oocyte degradation and follicular atresia, perturbed proper oogenesis, and ultimately resulted in subfertility. Our results reveal an important molecular mechanism of miR-17-92 in modulating murine oogenesis by targeting Bmf , which promotes germ cell loss during murine oogenesis [30]. These findings will assist in better understanding the etiology of disorders in oogenesis and in developing new therapeutic targets for female infertility.…”
Section: Discussionmentioning
confidence: 80%
“…Vaithiyanathan et al . reported that Bmf promoted germ cell loss during murine oogenesis [30]. Therefore, the detailed interaction between miR-19a and Bmf were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extensive depletion appears to be gonadotropin driven, and while the exact mechanisms are unknown, pubertal increases in the levels of FSH and LH that drive folliculogenesis are also likely to indirectly drive primordial follicle depletion, since GnRH antagonism during the peri-pubertal period prevents the significant primordial follicle loss that typically occurs during this time (103, 125, 126). Our sequencing data from the juvenile ovary did not reveal changes in the expression of BCL-2 modifying factor (BMF), which has recently been identified as a critical promoter of fetal oocyte and prepubertal primordial follicle loss (103, 127). However, differential expression of genes driving reproductive development and their potential regulation by FSH, as indicated by our upstream regulator analysis, warrant investigation of the quantity and quality of the follicle pool in the fetal and early postnatal GOAT KO ovary in future studies.…”
Section: Discussionmentioning
confidence: 70%